2004
DOI: 10.1073/pnas.0402153101
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of a cytoplasmic response regulator to the cell pole is linked to its cell cycle-regulated proteolysis

Abstract: The response regulator CtrA, which silences the Caulobacter origin of replication and controls multiple cell cycle events, is specifically proteolyzed in cells preparing to initiate DNA replication. At the swarmer-to-stalked cell transition and in the stalked compartment of the predivisional cell, CtrA is localized to the cell pole just before its degradation. Analysis of the requirements for CtrA polar localization and CtrA proteolysis revealed that both processes require a motif within amino acids 1-56 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 33 publications
0
71
1
Order By: Relevance
“…Degradation of CtrA is a highly specific event, only occurring before initiation of DNA replication. Localization and proper cell-cycle degradation of CtrA in vivo appear linked and require the presence of its N-terminal receiver domain and RcdA (14,33). Our results, however, show clearly that CtrA is efficiently degraded in an RcdA-independent reaction by purified ClpXP alone, with kinetics that account for the intracellular rate of CtrA degradation (Fig.…”
Section: Discussioncontrasting
confidence: 40%
“…Degradation of CtrA is a highly specific event, only occurring before initiation of DNA replication. Localization and proper cell-cycle degradation of CtrA in vivo appear linked and require the presence of its N-terminal receiver domain and RcdA (14,33). Our results, however, show clearly that CtrA is efficiently degraded in an RcdA-independent reaction by purified ClpXP alone, with kinetics that account for the intracellular rate of CtrA degradation (Fig.…”
Section: Discussioncontrasting
confidence: 40%
“…The regulated proteolysis of CtrA at the swarmer-to-stalked cell transition and in the stalked compartment of the predivisional cell requires multiple steps. These steps include the interaction with the RcdA degradation factor (3), the localization of both RcdA and CtrA to the stalked pole (3,8,11), the concomitant polar localization of ClpXP protease complex (3), and the physical interaction among ClpX, RcdA, and CtrA at that cell pole. Here, we have shown that the localization of ClpXP is essential for CtrA proteolysis, the CpdR single-domain response regulator mediates the dynamic polar localization and activity of the ClpXP protease, and the localization function of CpdR depends on its phosphorylation state.…”
Section: Discussionmentioning
confidence: 99%
“…ClpXP and its CtrA substrate are simultaneously localized to the stalked cell pole both at the swarmer-to-stalked cell transition and in the stalked cell compartment of the predivisional cell (3,8). We identify a single-domain response regulator, CpdR, that in its unphosphorylated state directs CtrA proteolysis by controlling ClpXP polar localization and activity.…”
mentioning
confidence: 99%
“…The Shapiro laboratory also demonstrated roles for Smc (structural maintenance of chromosomes), MreB, and topoisomerase IV in chromosomal organization in three other recent reports in PNAS (20)(21)(22). The widely conserved Smc has been shown in various systems to condense DNA and aid in successful segregation (23).…”
mentioning
confidence: 97%